Effect of weight reduction and cardiometabolic risk factor management on symptom burden and severity in patients with atrial fibrillation: a randomized clinical trial - Abed, Hany S; Wittert, Gary A; Leong, Darryl P; Shirazi, Masoumeh G; Bahrami, Bobak; Middeldorp, Melissa E; Lorimer, Michelle F; Lau, Dennis H; Antic, Nicholas A; Brooks, Anthony G; Abhayaratna, Walter P; Kalman, Jonathan M; et al. (JAMA : the journal of the American Medical Association, 2013)
Obesity is a risk factor for atrial fibrillation. Whether weight reduction and cardiometabolic risk factor management can reduce the burden of atrial fibrillation is not known. To determine the effect of weight reduction and management of cardiometabolic risk factors on atrial fibrillation burden and cardiac structure. Single-center, partially blinded, randomized controlled study conducted between June 2010 and December 2011 in Adelaide, Australia, among overweight and obese ambulatory patients (N = 150) with symptomatic atrial fibrillation. Patients underwent a median of 15 months of follow-up. Patients were randomized to weight management (intervention) or general lifestyle advice (control). Both groups underwent intensive management of cardiometabolic risk factors. The primary outcomes were Atrial Fibrillation Severity Scale scores: symptom burden and symptom severity. Scores were measured every 3 months from baseline to 15 months. Secondary outcomes performed at baseline and 12 months were total atrial fibrillation episodes and cumulative duration measured by 7-day Holter, echocardiographic left atrial area, and interventricular septal thickness. Of 248 patients screened, 150 were randomized (75 per group) and underwent follow-up. The intervention group showed a significantly greater reduction, compared with the control group, in weight (14.3 and 3.6 kg, respectively; P < .001) and in atrial fibrillation symptom burden scores (11.8 and 2.6 points, P < .001), symptom severity scores (8.4 and 1.7 points, P < .001), number of episodes (2.5 and no change, P = .01), and cumulative duration (692-minute decline and 419-minute increase, P = .002). Additionally, there was a reduction in interventricular septal thickness in the intervention and control groups (1.1 and 0.6 mm, P = .02) and left atrial area (3.5 and 1.9 cm2, P = .02). In this study, weight reduction with intensive risk factor management resulted in a reduction in atrial fibrillation symptom burden and severity and in beneficial cardiac remodeling. These findings support therapy directed at weight and risk factors in the management of atrial fibrillation. anzctr.org.au Identifier: ACTRN12610000497000.